Effect of speed endurance and strength training on performance, running economy and muscular adaptations in endurance-trained runners - Vorup, J.; Tybirk, J.; Gunnarsson, T. P.; Ravnholt, T.; Dalsgaard, S.; Bangsbo, J. (European Journal of Applied Physiology, 2016)
Purpose: To investigate the effects of combined strength and speed endurance (SE) training along with a reduced training volume on performance, running economy and muscular adaptations in endurance-trained runners. Methods: Sixteen male endurance runners (VO2-max: ~60 ml/kg/min) were randomly assigned to either a combined strength and SE training (CSS; n = 9) or a control (CON; n = 7) group. For 8 weeks, CSS replaced their normal moderate-intensity training (~63 km/week) with SE (2 ×/week) and strength training (2 ×/ week) as well as aerobic high (1 ×/ week) and moderate (1 ×/week) intensity training with a reduction in total volume of ~58 %, whereas CON continued their training (~45 km/week). Results: In CSS, 400-m and Yo-Yo intermittent recovery test performance was improved by 5 % (P < 0.01) and 19 % (P < 0.001), respectively, during the intervention period. Maximal aerobic speed was 0.6 km/h higher (P < 0.05), and maximal activity of lactate dehydrogenase subunits 1 and 2 was 17 % (P < 0.05) higher after compared to before the intervention period. Time to exhaustion and peak blood lactate during an incremental treadmill test was 9 % (P < 0.05) and 32 % (P < 0.01), respectively, higher and expression of Na+-K+ pump ß1 subunit was 15 % higher (P < 0.05) after compared to before the intervention period. 10-K performance, maximum oxygen uptake and running economy were unchanged. In CON, no changes were observed. Conclusions: Adding strength and speed endurance training, along with a reduced training volume, can improve short-term exercise capacity and induce muscular adaptations related to anaerobic capacity in endurance-trained runners.